(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study aimed to effects of aerobic exercise combined with resistance training on selected physical variables among middle aged working men. To facilitate the study thirty middle aged working men in Vinayaka Missions Research Foundation (Deemed to be University), Salem were randomly selected as population and their age was between 40 and 50 years. The population was from different categories of employment in the Vinayaka Mission’s Research Foundation. Before selecting as population, the population’ willingness to participate in the research program were got by explaining the usefulness of this research, the benefits of incorporating different training methods in the daily routine and the resultant health benefits.